Strategies for Gifted Students: Exploring Primary School Teachers’ Approaches - Antony, Soniya; Ramnath, R. (THE PRIMARY TEACHER, 2019)
This qualitative study explores how primary school teachers meet the needs of gifted children in regular classrooms. Six elementary school teachers were interviewed using a semi-structured approach, in Malappuram district, Kerala, India. The analysis of the study uncovered six themes that provide insightful perspectives on how primary school teachers perceive and comprehend giftedness. These themes shed light on teachers’ beliefs, attitudes, and practices related to gifted children, contributing to a deeper understanding of their perspectives. The themes highlight the multifaceted excellence of gifted students, the amplification of their exceptional qualities, the importance of empowering and nurturing their brilliance, and the need to create enriched learning environments that cater to their unique needs. The findings of this study provide valuable insights into how primary school teachers meet the needs of gifted students, thereby enhancing gifted students’ education in regular classrooms.